Analisis Efektifitas dan Efisiensi Manajemen keuangan di Aceh Barat - Alisman Alisman (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2014)
This study aims to analyze the efficiency and effectiveness of financial management in Aceh Barat in the era of autonomy. In addition, from expenditure side the analysis of this study evaluate whether the district budget of Aceh Barat was being used efficiently and effectively. The data used were secondary data from 2003 to 2012. The results of the study revealed that Aceh district is heavily influenced by public investment, economic growth, and the cost of tax collection. The level of budget management efficiency was ranging from 24.76%to 85.53%. This means that the budget efficiency in the district was somewhat efficient, while the level of effectiveness rangingfrom 96.32%to 117.78% which wasquite effective.